Pengaruh permainan tradisional ular naga dalam meningkatkan minat belajar siswa pada materi ragam budaya Indonesia di sekolah dasar - Regita Ayu Cahyani; Rosarina Giyartini; Anggit Merliana (IKIP Siliwangi, 2025)
This research was motivated by students' low interest in learning so that learning activities were not optimal. The stimulus given for implementing learning activities is still not appropriate, as can be seen from the low enthusiasm and active participation of students. So, based on these problems, the author attempts to use the traditional dragon snake game with the aim of finding out the effect of implementing the traditional dragon snake game in increasing students' interest in learning about various Indonesian cultural materials in elementary schools. The research method used is pre-experimental design in the form of a one group pretest-posttest design. Data collection techniques in this research include questionnaires, observation and documentation. The results of students' learning interest before being given treatment at the pretest were an average score of 59.00, while after being given treatment at the posttest the average score was 72.88. Based on this analysis, it shows a significant increase. Next, hypothesis testing is based on the results of the N-Gain increase data with a value of 0.66 which is included in the medium category. Then a t-test was carried out which gave a significance value of 0.000 which was less than 0.05 (0.000 < 0.05), so the hypothesis was accepted. So it can be concluded that students' interest in learning by using the traditional dragon snake game on various Indonesian cultural materials has increased with better results.